2012
DOI: 10.1073/pnas.1221046110
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitors increase glucocerebrosidase activity in Gaucher disease by modulation of molecular chaperones

Abstract: Gaucher disease is caused by mutations of the GBA gene that encodes the lysosomal enzyme glucocerebrosidase (GCase). GBA mutations often result in protein misfolding and premature degradation, but usually exert less effect on catalytic activity. In this study, we identified the molecular mechanism by which histone deacetylase inhibitors increase the quantity and activity of GCase. Specifically, these inhibitors limit the deacetylation of heat shock protein 90, resulting in less recognition of the mutant peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
72
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 38 publications
2
72
0
Order By: Relevance
“…Based interrupting its HSP90-mediated degradation while upregulating the molecular chaperone HSP70 and its associated cochaperone BCL2-associated athanogene 3 (BAG3) ( 48 ). These data are supported by additional studies in Gaucher's disease in which reduced ubiquitination and increased stability of mutant GCase was demonstrated after treatment with the HSP70-inducer/HSP90-inhibitors 17-N -allylamino-17-demethoxygeldanamycin, vorinostat, and LB-205 ( 45,50 ). Interestingly, the molecular mechanism of vorinostat and LB-205, which are both histone deacetylase inhibitors (HDACis), was recently clarifi ed, showing that both compounds inhibit the deacetylation of the middle domain of HSP90, resulting in less recognition of the mutant GCase, and hence less degradation, while increasing the amount of chaperones involved in folding, such as HSPA5 ( 45 ).…”
Section: Proteostasismentioning
confidence: 73%
See 1 more Smart Citation
“…Based interrupting its HSP90-mediated degradation while upregulating the molecular chaperone HSP70 and its associated cochaperone BCL2-associated athanogene 3 (BAG3) ( 48 ). These data are supported by additional studies in Gaucher's disease in which reduced ubiquitination and increased stability of mutant GCase was demonstrated after treatment with the HSP70-inducer/HSP90-inhibitors 17-N -allylamino-17-demethoxygeldanamycin, vorinostat, and LB-205 ( 45,50 ). Interestingly, the molecular mechanism of vorinostat and LB-205, which are both histone deacetylase inhibitors (HDACis), was recently clarifi ed, showing that both compounds inhibit the deacetylation of the middle domain of HSP90, resulting in less recognition of the mutant GCase, and hence less degradation, while increasing the amount of chaperones involved in folding, such as HSPA5 ( 45 ).…”
Section: Proteostasismentioning
confidence: 73%
“…As mentioned above, the potential benefi t of modulation of the HSR is now emerging in the LSD fi eld with the reporting of a number of studies of this approach in genetically distinct diseases such as Gaucher's disease, Tay-Sach's disease, Niemann-Pick disease types A and B, Niemann-Pick disease type C, ␣ -mannosidoses, sialidosis, and mucopolysaccharidosis type 3A ( 7,(43)(44)(45)(46)(47)(48)(49). In cellular studies of Gaucher's and Tay-Sach's disease for example, the induction of the HSR or UPR with celastrol and MG-132 results in increases of both cytosolic and ER-resident chaperones, of the HSP70 family in particular, in a process dependent on UPRresponsive transcription factors Ire1, ATF6, and PERK.…”
Section: Proteostasismentioning
confidence: 99%
“…Our previous findings demonstrated that mutations in GCase result in its binding to Hsp90 (18,19). Recognition by Hsp90 initiates protein degradation through the ERAD and valosin-containing protein (VCP)/protein 97 (p97)/ proteasome pathways (7,(19)(20)(21).…”
Section: Celastrol Targets the Chaperone Function Of Hsp90 And Inhibimentioning
confidence: 99%
“…Interfering with the function of Hsp90 has been shown to reduce the degradation of GCase (19). Zhang et al (16) showed that celastrol interferes with Hsp90 function by occupying a specific…”
Section: Celastrol Targets the Chaperone Function Of Hsp90 And Inhibimentioning
confidence: 99%
See 1 more Smart Citation